Adding value to first-year undergraduate marketing education: team-based learning as a strategic response to changing modern educational environments. (23rd February 2017) - Carrie, Douglas G.; Mulla, Parizad; Patterson, Andrew; Kilkolly-Proffit, Michelle; Brookes, Richard; Sima, Herbert; Agee, Tom
Abstract: This paper explains the University of Auckland Business School's strategic response to a rapidly changing global educational environment through the redevelopment of its first-year core undergraduate curricula experience. Central to this was the decision to adopt team-based learning (TBL) as a key component in the design and delivery of a new approach. Not simply adding value to marketing education, the delivery of its first-year academic content is from a highly interdisciplinary perspective, thereby substantially differentiating it from traditional 'Marketing 101'. This adoption of TBL emphasizes a strategic focus on achieving three key objectives: to take an integrated and interdisciplinary approach to the first-year undergraduate business experience; to embed a strong focus on the development of students' academic and professional skills; and to place a strong focus on supporting the first-year transition. The paper details the implementation of this strategy and its subsequent and ongoing continuous improvement processes. It contributes to the literature on TBL by demonstrating the strategic benefits and challenges of a large-scale implementation, and the successful integration of content, graduate capabilities and transitional goals.